CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG (Studi Pada Mahasiswa Universitas Trunojoyo Madura)” - Badwi, Moh; Setiyo Pambudi, Bambang (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
Moh Badwi, Influence of Brand Image and Price on Samsung Smartphone Purchase Decisions (Case Study in Trunojoyo Madura University Students) under the guidance of Dr. Bambang Setiyo Pambudi, S.E.,M.M. The aim of this study is to find out the influence of brand image and price on the purchase decision of Samsung smartphone at the University of Trunojeo Madura. Research methods use quantitative methods. The data used is primary data. The research data was obtained by spreading a questionnaire using the Likert scale using a sample of 97 respondents. The research uses the purposive sampling technique method and the analytical tool used is double linear regression with the help of the SPSS Version 16.0 program using the double lineary regression analysis technique. The partial test results showed that brand image and price have a positive influence but within a small scope on purchase decisions. For simultaneous tests, it showed the combined image of brand and price has a positive and significant influence on purchasing decisions. The determination coefficient value of 0.368 means that the regression model obtained can explain that brand image and price variables can influence purchasing decisions by 36.8% The rest is influenced by other variables not described in this study.